Greater Short-Time Recovery of Peripheral Fatigue After Short- Compared With Long-Duration Time Trial - Froyd, Christian; Beltrami, Fernando G.; Millet, Guillaume Y.; MacIntosh, Brian R.; Noakes, Timothy D. (Frontiers in Physiology, 2020)
The kinetics of recovery from neuromuscular fatigue resulting from exercise time-trials (TT) of different durations are not well known. The aim of this study was to determine if TTs of three different duration would result in different short-term recovery in MVC and evoked peak forces. Twelve trained subjects performed repetitive concentric right knee extensions on an isokinetic dynamometer self-paced to last 3, 10, and 40 min (TTs). Neuromuscular function was assessed immediately (< 2 s) and 1, 2, 4 and 8 min after completion of each TT using maximal voluntary contractions (MVC) and electrical stimulation. Electrical stimulations consisted of single stimulus (SS), paired stimuli at 10 Hz (PS10), and paired stimuli at 100 Hz (PS100). Electrically evoked forces including the ratio of low to high frequency doublets were similar between trials at exercise cessation, but subsequently increased more (P < 0.05) after the 3-min TT compared with either the 10-min or 40-min TT when measured at one or two minutes of recovery. MVC force was not different between trials. The results demonstrate that recovery of peripheral fatigue including low-frequency fatigue depends on the duration and intensity of the preceding self-paced exercise. These differences in recovery probably indicate differences in the mechanisms of fatigue for these different time-trials. Since recovery is faster after a 3-min TT than a 40-min TT, delayed assessment of fatigue will detect a difference in peripheral fatigue between trials that was not present at exercise cessation.